A Modified Model of Axial Flux Permanent Magnet Generator for Wind Turbine Applications - Ashraf, M. M.; Malik, T. N. (The Nucleus, 2014)
The Axial Flux Permanent Magnet Generators (AFPMGs) are gaining immense attention in the modern era. The single stage AFPMG topology consists of one stator disc which is held stationery between two revolving rotor discs attached with a common shaft. The number of poles of AFPMG depends on the winding pattern in which the coils are connected in series within stator disc. Connecting the coils in begin-to-end winding pattern, doubles the number of poles which also increases the active mass of AFPMG. The AFPMG considering begin-to-end winding pattern, can be operated at half shaft speed. This AFPMG is also having greater air gap flux density which, ultimately, improves the power density parameter of AFPMG. In this paper, a modified AFPMG has been proposed which is designed by considering begin-to-end winding pattern. A 380W single phase, single stage prototype model has been developed and tested. The test results show that power density of designed AFPMG with begin-to-end winding pattern has been improved by 32% as compared to AFPMG with begin-to-begin winding pattern. The proposed low speed and high power density AFPMG model can be actively deployed for wind turbine applications.